2023
DOI: 10.1002/anie.202216102
|View full text |Cite
|
Sign up to set email alerts
|

Organic Additive‐derived Films on Cu Electrodes Promote Electrochemical CO2 Reduction to C2+ Products Under Strongly Acidic Conditions

Abstract: Electrochemical CO 2 reduction (CO 2 R) at low pH is desired for high CO 2 utilization; the competing hydrogen evolution reaction (HER) remains a challenge. High alkali cation concentration at a high operating current density has recently been used to promote electrochemical CO 2 R at low pH. Herein we report an alternative approach to selective CO 2 R (> 70 % Faradaic efficiency for C 2 + products, FE C2 + ) at low pH (pH 2; H 3 PO 4 /KH 2 PO 4 ) and low potassium concentration ([K + ] = 0.1 M) using organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 52 publications
0
48
0
Order By: Relevance
“…23 During the course of this work, another study was published, showing a comparable effect with Cu electrodes modified with pyridinium. 26 This was achieved here thanks to an easy electrodeposition of a stable imidazolium-based layer on the surface of CuNPs, which was shown to inhibit HER and C 1 products formation and favor instead ethylene and ethanol formation. While a positive charge on the surface, actually mimicking a K + layer, may explain the HER inhibition effect, the mechanism by which the organic layer favors C-C coupling is less clear at present.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 During the course of this work, another study was published, showing a comparable effect with Cu electrodes modified with pyridinium. 26 This was achieved here thanks to an easy electrodeposition of a stable imidazolium-based layer on the surface of CuNPs, which was shown to inhibit HER and C 1 products formation and favor instead ethylene and ethanol formation. While a positive charge on the surface, actually mimicking a K + layer, may explain the HER inhibition effect, the mechanism by which the organic layer favors C-C coupling is less clear at present.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…During the course of this work, another study reported the promotion of C 2+ product formation by the deposition of a molecular film derived from a pyridinium salt on Cu under acidic conditions (pH = 2). 26 The choice of an imidazolium salt, as a proof of concept regarding the impact of Cu surface modification on CO 2 RR selectivity during acidic electrolysis, was based on previous results, including some from our laboratory. 27−30 The very first studies were carried out with Ag 31−35 and Au 36,37 catalysts, showing a positive impact of the addition of IL (either in solution or drop-cast on the electrode surface) on overpotentials and the selectivity (CO 2 RR to CO vs HER).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Experimentally, CO 2 reduction has been extensively investigated in the presence of organic cations of various types, including surfactants, , ionomer films, and cationic conjugate bases of superacids . However, in all these studies, the organic cation is present as a minor constituent of the medium alongside either a super-stoichiometric excess of alkali metal cations for studies in neutral pH electrolytes (Figure b, top) or in the presence of a super-stoichiometric excess of hydronium ions for studies in bulk acidic electrolytes .…”
Section: Introductionmentioning
confidence: 99%
“…Because each mode of promotion would motivate distinct approaches to electrolyte design, addressing this knowledge gap is critical for systematic improvements to CO2RR efficiency and selectivity. Experimentally, CO2 reduction has been extensively investigated in the presence of organic cations of various types, including surfactants 22,23 , ionomer films [24][25][26][27][28][29][30] , and cationic conjugate bases of superacids 31 . However, in all these studies, the organic cation is present as a minority constituent of the medium alongside either a super-stoichiometric excess of alkali metal cations for studies in neutral pH electrolytes (Figure 1b, top) or in the presence of super-stoichiometric excess of hydronium ions for studies in bulk acidic electrolyte 32 .…”
Section: Introductionmentioning
confidence: 99%